Perawatan Kaki Dalam Pencegahan Neuropaty Pada Pasien Diabtes Mellitus di Puskemas Andalas - Rasyid, Willady; Hidayatul Rahmi (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
Andalas Public Health Center is a health facility experiencing a continual increase in diabetes mellitus cases each year. Diabetes mellitus is the most commonly treated disease at the Andalas Health Center. Given the high incidence of diabetes, comprehensive management is essential, particularly at the Andalas Health Center, to prevent diabetes-related complications. The main issues identified include the lack of healthcare personnel to provide health education on diabetes complication prevention, as well as patients’ limited knowledge and poor behavior regarding foot care. The goal of this community service program is to provide education and explanation about the importance of foot care in preventing neuropathy. It is expected that patients will be able to perform foot care independently, thereby reducing the risk of neuropathy. This community service activity wasconducted at the Andalas Public Health Center in Padang with 20 participants in January 2025. The speaker and team provided a health education session titled: "Foot Care in the Prevention of Neuropathy in Patients with Diabetes Mellitus." The activity was well received and attended enthusiastically by the patients. During the session, the speaker and the team divided roles and responsibilities to ensure the smooth delivery of the health education and materials. As a result, 90% of the participants were able to understand, implement, and perform proper foot care techniques for diabetes in their daily lives.